STUDY OF MEMBRANE AERATED BIOREACTOR ADVANCES AND APPLICATION - Lerian Friatnasary, Dwi
The membrane aerated bioreactor (MABR) has been considered as an innovative technology to solve the problems raised in the conventional wastewater treatment process using activated sludge process, such as low nutrient and pollutant removal rate, foam formation, and biological instability. However, the MABR operation still has a problem, which is the limitation of controlling the thickness of the biofilm, which can result in a decreasing MABR performance. Therefore, this literature review aims to acknowledge the role of the membrane in MABR, the effect of operating condition on MABR performance, the biofilm formation and control, the application of MABR in wastewater treatment, and the prospect of MABR. Based on the review that has been done, MABR is proven to be able to increase the removal efficiency of carbon, nitrogen, and pollutants. It is because the use of gas-permeable membranes can enhance the oxygen transfer rate to the biofilm so that the biodegradation process is carried out optimally. Besides, the membranes also act as a support for attached-biofilm growth. Several studies have been conducted to control the biofilm thickness, including increasing shear stress, adding chemicals, and using biological predators to control the growth of microorganisms. Although the chemical addition and the use of biological predator methods still lack in terms of automation, they are proven to reduce the thickness of the biofilm. MABR has been widely applied to treat wastewater from various sectors, including municipal to high strength wastewater, so the technology has the potential to be developed on a commercial scale.